An Evaluation to assess the Knowledge regarding Prevention and Management of Chickenpox in Children among Mothers having Children below 10 years of age residing at selected community area of Allahabad (India) - Joseph, Jemy Elizabeth; Mathew, Shiju (International Journal of Advanced Nursing Studies, 2013)
Chickenpox is a worldwide disease and is no respecter race or class. The incidence increases in spring & winter months in the temperate zones. In the tropics, the peak incidence is during winter and early spring. The disease in fact started spreading from February itself. Lack of knowledge among common people on preventing water contamination is helping the virus to spread rapidly. The descriptive study attempts to assess the knowledge regarding prevention and management of chickenpox among mothers of below 10 years of age children who are residing at Naini, Allahabad with a view to develop an information booklet. Method: The study involved single group test without a control, using non-experimental descriptive design, with non-probability convenient sampling. 60 women were involved in data collection by using structured questionnaire. The study came to an end by implementation of information booklet on chickenpox and its prevention and management, and the results were described using descriptive and inferential statistics. Results: The overall mean knowledge score was found to be 48.86 % and S.D 5.87. The highest mean knowledge score was found on general health (46.5%). The mean knowledge score varied from 46.5% to 55.6% on different aspects of chickenpox. Chi-square test implies that there was a statistically significant association between selected demographic variables with knowledge of prevention and home care management of chickenpox at 5 percent level. Conclusion: The overall findings of the study clearly showed that there is lack of knowledge of prevention and home care management of chickenpox among mothers and the results revealed that distribution of information booklet on chickenpox and its prevention and management will be helpful for the women to gain knowledge.